(untitled) (Perner’s Contacts, 2011)
Transport is significantly influenced by its external milieu, and, at the same time, it itself affects this milieu. The interaction can be observed in political, legislative, economic, social, cultural, or technological fields. The strongest impacts are connected with the environment. Climatic changes, which the transport sector contributes to, have negative retroactive effects on transport systems. In this context it is necessary to deal with transport sustainability, and search for ways how to reduce this negative interaction.